The Impact of Coping Styles and Gender on Situational Coping: An Ecological Momentary Assessment Study With the mHealth Application TrackYourStress - O’Rourke, Teresa; Vogel, Carsten; John, Dennis; Pryss, Rüdiger; Schobel, Johannes; Haug, Fabian; Haug, Julian; Pieh, Christoph; Nater, Urs M.; Feneberg, Anja C.; Reichert, Manfred; Probst, Thomas (Frontiers in Psychology, 2022)
The aim of this study was to investigate the impact of different coping styles on situational coping in everyday life situations and gender differences. An ecological momentary assessment study with the mobile health app TrackYourStress was conducted with 113 participants. The coping styles Positive Thinking, Active Stress Coping, Social Support, Support in Faith, and Alcohol and Cigarette Consumption of the Stress and Coping Inventory were measured at baseline. Situational coping was assessed by the question “How well can you cope with your momentary stress level” over 4 weeks. Multilevel models were conducted to test the effects of the coping styles on situational coping. Additionally, gender differences were evaluated. Positive Thinking (p = 0.03) and Active Stress Coping (p = 0.04) had significant positive impacts on situational coping in the total sample. For women, Social Support had a significant positive effect on situational coping (p = 0.046). For men, Active Stress Coping had a significant positive effect on situational coping (p = 0.001). Women had higher scores on the SCI scale Social Support than men (p = 0.007). These results suggest that different coping styles could be more effective in daily life for women than for men. Taking this into account, interventions tailored to users’ coping styles might lead to better coping outcomes than generalized interventions.